Application of code of conduct sanctions against notary officials sentenced to prison - Shabril Ahmad Thaariq; Frengki Hardian; Chandra Yusuf (Jurnal Info Sains : Informatika dan Sains, 2024)
Notary is a general official who is authorized to make an Authentic Deed to carry out his duties and functions in serving the community, Notaries are Members of the Association, namely the Indonesian Notary Association (INI) and Notaries are subject to the Code of Ethics, and are supervised by the Supervisory Council, but do not close the fact that there are still Notaries who violate the Code of Ethics, even commit criminal acts, and there are Notaries after leaving prison continue to carry out their positions, The method used is normative juridical research, which is conducting legal research by reviewing library materials or secondary data as a basis for research.The Indonesian Notary Association is the Notary Honorary Council which is authorized to allow or not allow the authorities, courts, prosecutors to process laws against Notaries involved in a case